Contrasting adaptation responses by squatters and low-income tenants in Khulna, Bangladesh - Roy, Manoj; Hulme, David; Jahan, Ferdous (© 2013 International Institute for Environment and Development, 2016)
This article was published in the Journal of Environment and Urbanization [ © 2013 International Institute for Environment and Development (IIED) ] and the definite version is available at: https://doi.org/10.1177/0956247813477362. The book chapter's website is at: http://journals.sagepub.com/doi/abs/10.1177/0956247813477362